2016
DOI: 10.1016/j.jbiomech.2015.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Differential ascending and descending aortic mechanics parallel aneurysmal propensity in a mouse model of Marfan syndrome

Abstract: Marfan syndrome (MFS) is a multi-system connective tissue disorder that results from mutations to the gene that codes the elastin-associated glycoprotein fibrillin-1. Although elastic fibers are compromised throughout the arterial tree, the most severe phenotype manifests in the ascending aorta. By comparing biaxial mechanics of the ascending and descending thoracic aorta in a mouse model of MFS, we show that aneurysmal propensity correlates well with both a marked increase in circumferential material stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 27 publications
11
44
0
Order By: Relevance
“…In addition to our newly collected biaxial data on Tsc1 f/f þ Tmx, ApoE 2/2 þ HT, Fbln4 SMKO , elastase-exposed and control ascending aortas, we previously reported similar data for five other models [16][17][18]20]: Myh11 R247C/R247C , Myh11 R247C/R247C þ HT, Tgfbr2 f/f þ Tmx, Fbn1 mgR/mgR and Fbln5 2/2 . Collectively, these 10 models represent diverse aortic phenotypes (table 1), ranging from normal (Control) to a stiffer and lengthened aorta without a propensity to form aneurysms (Fbln5 2/2 ), a mild phenotype (Myh11 R247C/R247C ) with little dilatation that is yet vulnerable to dissections when rendered hypertensive (Myh11 R247C/R247C þ HT), a moderate phenotype at young ages with some dilatation that develops aneurysms later in life (Tsc1 f/f þ Tmx), a dissection-prone vessel (Tgfbr2 f/f þ Tmx), a vessel with dramatic dilatation despite wall thickening (ApoE 2/2 þ HT) and ultimately ones with marked aneurysmal development (Fbn1 mgR/mgR and Fbln4 SMKO ).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition to our newly collected biaxial data on Tsc1 f/f þ Tmx, ApoE 2/2 þ HT, Fbln4 SMKO , elastase-exposed and control ascending aortas, we previously reported similar data for five other models [16][17][18]20]: Myh11 R247C/R247C , Myh11 R247C/R247C þ HT, Tgfbr2 f/f þ Tmx, Fbn1 mgR/mgR and Fbln5 2/2 . Collectively, these 10 models represent diverse aortic phenotypes (table 1), ranging from normal (Control) to a stiffer and lengthened aorta without a propensity to form aneurysms (Fbln5 2/2 ), a mild phenotype (Myh11 R247C/R247C ) with little dilatation that is yet vulnerable to dissections when rendered hypertensive (Myh11 R247C/R247C þ HT), a moderate phenotype at young ages with some dilatation that develops aneurysms later in life (Tsc1 f/f þ Tmx), a dissection-prone vessel (Tgfbr2 f/f þ Tmx), a vessel with dramatic dilatation despite wall thickening (ApoE 2/2 þ HT) and ultimately ones with marked aneurysmal development (Fbn1 mgR/mgR and Fbln4 SMKO ).…”
Section: Discussionsupporting
confidence: 65%
“…Despite data confirming that the smooth muscle myosin heavy chain (MYH11) variant R247C disrupts contraction of aortic smooth muscle cells [13], this variant has minimal effects on gross anatomy (figure 1g), microstructure (figure 1q) and mechanical behaviour (figure 1a-d) of the ascending aorta in the mouse (Myh11 R247C/R247C ). Hypertension induced via a high-salt diet in combination with L-NAME can cause aortic dissections in these mice [16], but the non-dissected samples studied herein after 18 Table 1. Physiological data (mean + s.e.m.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bellini et al recently reported differences in biaxial mechanical properties of the ascending versus descending thoracic aorta that are consistent with a propensity for aneurysms to form in the ascending segment. 5 Further studies are required to assess regional variations in vascular mechanics with losartan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent biomechanical analyses of Fbn1 mgR/mgR mice have raised the possibility that a structurally impaired aortic matrix may perturb AT1R mechanosignaling (72, 73). Characterization of cardiomyopathy in Fbn1 mgR/mgR mice has in dependently supported this notion (74).…”
Section: Tgf-β and Angiotensin II Signaling In Thoracic Aortic Diseasementioning
confidence: 99%